Relapse of Multiple Myeloma Presenting as Extramedullary Plasmacytomas in Multiple Organs - Murat Köse; Ersida Buraniqi; Timur Selçuk Akpinar; Seyit Mehmet Kayacan; Tufan Tükek (Case Reports in Hematology)
Multiple myeloma is a neoplastic plasma cell disorder. It is characterized by collections of abnormal plasma cells accumulating in the bone marrow, where they interfere with the production of normal blood cells. It usually presents as a multisystemic involvement, whose symptoms and signs vary greatly. Some patients have slowly progressive disease while others have aggressive clinical behavior by extramedullary involvement. In addition to renal failure, anemia, hypercalcemia, lytic bone lesions, and immunodeficiency, it also affects multiple organ system, such as pancreas, adrenal glands, kidney, skin, lung, liver, spleen, lymph nodes, and bone. To raise awareness of the variable presentations of this disease, we report a 53-year-old male patient, with multiple myeloma in his first remission who relapsed with extramedullary plasmacytomas (EMPs) involving multiple organs, such as pancreas, adrenal glands, kidney, skin, lung, liver, spleen, and lymph nodes.